Extracorporeal Hemadsorption versus Glucocorticoids during Cardiopulmonary Bypass: A Prospective, Randomized, Controlled Trial - Gordana Taleska Stupica; Maja Sostaric; Marija Bozhinovska; Lea Rupert; Zoran Bosnic; Ales Jerin; Alojz Ihan; Tomislav Klokocovnik; Matej Podbregar (Cardiovascular Therapeutics)
Extracorporeal hemadsorption may reduce inflammatory reaction in cardiopulmonary bypass (CPB) surgery. Glucocorticoids have been used during open-heart surgery for alleviation of systemic inflammation after CPB. We compared intraoperative hemadsorption and methylprednisolone, with usual care, during complex cardiac surgery on CPB, for inflammatory responses, hemodynamics, and perioperative course. Seventy-six patients with prolonged CPB were recruited and randomized, with 60 included in final analysis. Allocation was into three groups: Methylprednisolone (n = 20), Cytosorb (n = 20), and Control group (usual care, n = 20). Proinflammatory (TNF-α, IL-1β, IL-6, and IL-8) and anti-inflammatory (IL-10) cytokines which complement C5a, CD64, and CD163 expression by immune cells were analyzed within the first five postoperative days, in addition to hemodynamic and clinical outcome parameters. Methylprednisolone group, compared to Cytosorb and Control had significantly lower levels of TNF-α (until the end of surgery, p<0.001), IL-6 (until 48 h after surgery, p<0.001), and IL-8 (until 24 h after surgery, p<0.016). CD64 expression on monocytes was the highest in the Cytosorb group and lasted until the 5th postoperative day (p<0.016). IL-10 concentration (until the end of surgery) and CD163 expression on monocytes (until 48 h after surgery) were the highest in the Methylprednisolone group (p<0.016, for all measurements between three groups). No differences between groups in the cardiac index or clinical outcome parameters were found. Methylprednisolone more effectively ameliorates inflammatory responses after CPB surgery compared to hemadsorption and usual care. Hemadsorption compared with usual care causes higher prolonged expression of CD64 on monocytes but short lasting expression of CD163 on granulocytes. Hemadsorption with CytoSorb® was safe and well tolerated. This trial is registered with clinicaltrials.gov (NCT02666703).